Prevalence and Causes of Blindness and Visual Impairment in Sokoto State, Nigeria: Baseline Data for Vision 2020: The Right to Sight Eye Care Programme - Muhammad, Nasiru (Medknow Publications, 2011)
PURPOSE: To estimate the prevalence of low vision and blindness, identify the causes, and suggest policies for an effective eye care program based on 2005 data from Sokoto State, Nigeria. MATERIALS AND METHODS: A stratified two-stage cluster sampling method was used to quantify the prevalence of blindness and the causes from 4 health zones in Sokoto State. Subjects were evaluated using a magnifying loupe, direct ophthalmoscope and torchlight. Data were collected based on the World Health Organization prevention of blindness coding for an eye examination. Prevalences with 95% confidence intervals (CI) were calculated and surgical coverage for causes of blindness was also analyzed. RESULTS: The response rate was 91%. The prevalence of bilateral blindness was 1.9% (95% CI: 1.5–2.3%) ranging from 1.6% to 2.0% across the four health zones. The prevalence was 2.1% (95% CI: 1.6–2.6%) in males and 1.6% (95% CI: 1.1–2.1%) in females. The leading cause of bilateral blindness was cataract (51.6%), followed by uncorrected aphakia (20.9%) and glaucoma (11%). The prevalence of bilateral operable cataract was 1.9% (95% CI: 1.5–2.3%). The cataract surgical coverage (individuals with visual acuity <6/60) for the study was lower than the couching coverage (4.4% vs. 14.9%, respectively). Surgical coverage for trichiasis was 4.4%. The major barrier to cataract and glaucoma management was cost. CONCLUSIONS: The prevalence of blindness in Sokoto State is high yet the main causes are largely avoidable. Barriers can be reduced by appropriate health education regarding the eye care program and the provision of integrated, sustainable, affordable and equitable services.